Analisis Peramalan Persediaan Bahan Baku dalam Meningkatkan Kapasitas Produksi pada Usaha Panglon UD. Nelvan di Desa Fulolo Lalai, Kecamatan Hiliserangkai - Mendrofa, Heldi Usia Fransih; Gea, Jeliswan Berkat Iman Jaya; Zebua, Serniati; Zai, Kurniawan Sarototonafo (Universitas Medan Area, 2025)
This study aims to determine the forecasting of raw material inventory to optimize production capacity at the UD. Nelvan panglong business. The background of this study is based on the difficulty in providing limited raw materials, which hampers production capacity. The research method used in this study is quantitative with a descriptive approach. The data used in this study is secondary data in the form of raw material ordering records for 16 months, so the population and sample are raw material recording reports. The data analysis technique used is the Exponential Smoothing method. The results of the study indicate that a systematic forecasting system has not been used at the study site. Based on calculations using the Exponential Smoothing method with α = 0.1, it provides better results with an average error of 10.898 and an estimated raw material order of 489.59 m3 in the following month compared to α = 0.3 and 0.5. The results of this study recommend applying this method in determining the amount of raw material orders each period to avoid raw material stock shortages so that business operations can continue to run smoothly and be able to meet consumer or customer demand.